Graphene oxide shell-isolated Ag nanoparticles for surface-enhanced Raman scattering. (January 2015) - Chen, Shaona; Li, Xin; Zhao, Yuanyuan; Chang, Limin; Qi, Jingyao
Abstract: An efficient surface enhanced Raman scattering (SERS) substrate has been developed based on Ag nanoparticle-decorated graphene oxide (GO). The structure of Ag@GO hybrid material was confirmed by X-ray diffraction, transmission and scanning electron microscopy. The as-prepared substrate exhibited the enhancement ability of SERS toward various aromatic dyes, such as Rhodamine 6G, Rhodamine B, and crystal violet. The enhanced Raman signals could be due to the presence of an ultrathin GO shell with 2.8 nm in thickness. In particular, the GO shell could efficient to maintain chemical and optical stability, and improved biocompatibility for this SERS-activity material.